Combining hypoxic methods for peak performance - Millet, G. P.; Roels, B.; Schmitt, L.; Woorons, X.; Richalet, J. P. (Sports Medicine, 2010)
New methods and devices for pursuing performance enhancement through altitude training were developed in Scandinavia and the USA in the early 1990s. At present, several forms of hypoxic training and/or altitude exposure exist: traditional `live high-train high` (LHTH), contemporary `live high-train low` (LHTL), intermittent hypoxic exposure during rest (IHE) and intermittent hypoxic exposure during continuous session (IHT). Although substantial differences exist between these methods of hypoxic training and/or exposure, all have the same goal: to induce an improvement in athletic performance at sea level. They are also used for preparation for competition at altitude and/or for the acclimatization of mountaineers.